2018
DOI: 10.1590/1807-1929/agriambi.v22n11p799-803
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative loss of tomato fruits during mechanized harvest

Abstract: The use of mechanization in the harvesting of industrial tomatoes provides greater yield and speed of this stage. However, mechanical intervention in this process may alter the physiology of harvested fruits. Therefore, the objective of this study was to measure the quantitative losses of tomato fruits and to verify the physico-chemical behavior of fruits harvested based on physicochemical analysis in harvesters with different hours of use. Three self-propelled harvesters of the same brand and model with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The higher the fruit firmness, the lower the losses caused during harvesting and transportation to the industry (Luz et al, 2016). Machado et al (2018) The hybrid BRS Sena produces tomatoes with reasonable SS; however, Nascimento et al (2013) reported that SSC in fruits may be a genetic characteristic of the cultivar, but can be affected by temperature, irrigation, and fertilizer application (Branches et al 2013),…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the fruit firmness, the lower the losses caused during harvesting and transportation to the industry (Luz et al, 2016). Machado et al (2018) The hybrid BRS Sena produces tomatoes with reasonable SS; however, Nascimento et al (2013) reported that SSC in fruits may be a genetic characteristic of the cultivar, but can be affected by temperature, irrigation, and fertilizer application (Branches et al 2013),…”
Section: Resultsmentioning
confidence: 99%
“…The soil used was classified as a Typic Hapludox (Latossolo Vermelho Eutrofico tipico;Santos et al, 2018) of mean texture. Soil samples of the 0-20 cm layer were collected for analysis, which presented the following characteristics: pH in water = 6.6; organic matter = 1.7 dag kg -1 (colorimetry); P = 5.6 mg dm -3 (Mehlich-1); K = 189 mg dm -3 (Mehlich-1); Ca = 3.5 cmol c dm -3 (KCl 1mol L -1 ); Mg = 1.0 cmol c dm -3 (KCl 1mol L -1 ); Al = 0.0 cmol c dm -3 (KCl 1mol L -1 ); H+Al = 1.5 cmol c dm -3 (pH SMP); base saturation = 77%; aluminum saturation = 0%; P rem = 42.7 mg L -1 (equilibrium solution P); sand = 66 dag kg -1 ; silt = 9 dag kg -1 ; and clay = dag kg -1 .…”
Section: Methodsmentioning
confidence: 99%
“…The hardness value of 'Optima' tomatoes decreased in all treatments during storage. According to Machado et al (2018), a high level of physical damage causes the hardness value of the fruit to decrease or the fruit to become softer and has a high percentage of fruit weight loss. Additionally, physical damage increases the rate of respiration, ethylene production, and biochemical reactions cause changes in color, texture, and quality of the chemical content in the fruit.…”
Section: Resultsmentioning
confidence: 99%
“…Tomato (Solanum lycopersicum) is a very sensitive food commodity for harvesting, transportation and processing [6]. Tomatoes are a climacteric product which means ripening may occurs after detached from the plant.…”
Section: Introductionmentioning
confidence: 99%